Jenis Kelamin sebagai Variabel Moderasi terhadap Hubungan Lingkungan Kerja dengan Kepuasan Kerja Karyawan - Tommy Christianto Suryana; Berta Esti Ari Prasetya (Universitas Muhammadiyah Jember, 2021)
Work is an essential thing in the world of work so that many studies have been carried out to examine the variables that are correlated with it. In this study, the researcher wanted to examine the relationship between work environment and job satisfaction and gender as a moderating variable for employees at the Yogya Cherbon Junction department store. This research is quantitative research with a survey method, using two measuring tools, namely: the Job Satisfaction Scale by Brayfield Rothe (1951) and the Work Environment Scale from Moos (in Maqsood, 2011). The study involved 119 employees of the Yogya Cherbon Junction Department Store, consisting of 17 men and 102 women. The results of the analysis of the R-value data of 0.512 and F of 13.614 with a significance of 0.000 (p 0.05), which indicates a positive correlation between the work environment and significant job satisfaction. However, it was found that the value on X3 (interaction between work environment variables and gender) was 1.486 with a significance of 0.140 (p0.05), which indicates that gender does not apply as a variable to the relationship between job satisfaction and the work environment of employees at the Yogya Intersection Department Store. Carbon. Further explanation of the results is discussed in this article, along with suggestions that can be implemented for the world of work based on this research